Failure prediction of composite sandwich L-joint under bending. (1st August 2018) - Zeng, Haiyan; Yan, Renjun; Xu, Lin
Abstract: This article studies failure prediction of composite sandwich L-joint under bending. Five specimens have been tested to failure and numerical model has been established to predict load bearing capacity of such joint. Progressive damage model (PDM) technique is used in numerical simulation. Failure load and damage locations via numerical modelling have been experimentally verified. Relationship between failure load and geometric parameters of stiffener has been established based on dimensional analysis. Based on the comparison with FEM prediction and test result, it has been validated that the proposed expression is capable of predicting failure load with certain accuracy. Influence of each geometric parameter is clearly shown in the expression and the proposed model provides a reference for joint design.